Synthesis and Characterization of Poly(lactic-co-glycolic) Acid Nanoparticles-Loaded Chitosan/Bioactive Glass Scaffolds as a Localized Delivery System in the Bone Defects. (11th May 2014) - Nazemi, K.; Moztarzadeh, F.; Jalali, N.; Asgari, S.; Mozafari, M.
Abstract : The functionality of tissue engineering scaffolds can be enhanced by localized delivery of appropriate biological macromolecules incorporated within biodegradable nanoparticles. In this research, chitosan/58S-bioactive glass (58S-BG) containing poly(lactic-co-glycolic) acid (PLGA) nanoparticles has been prepared and then characterized. The effects of further addition of 58S-BG on the structure of scaffolds have been investigated to optimize the characteristics of the scaffolds for bone tissue engineering applications. The results showed that the scaffolds had high porosity with open pores. It was also shown that the porosity decreased with increasing 58S-BG content. Furthermore, the PLGA nanoparticles were homogenously distributed within the scaffolds. According to the obtained results, the nanocomposites could be considered as highly bioactive bone tissue engineering scaffolds with the potential of localized delivery of biological macromolecules.